The Factors That Auditor Switching On Go Public Company In Indonesia(Empirical Study on Manufacture Company Which Registered on Indonesia Stock Exchange In 2009-2014) - Cristikawati, Cristikawati, Drs. Wahyono, Ak., MA (2016)
Independence of the public accounting firm will fade when the suspect had long-standing relationships with its client. One way to keep independence auditor is to make the turn public accounting firm. Several previous studies showed the results of different studies. This study aims to examine and obtain empirical evidence about the factors that affect the company went public did turn public accounting firm in Indonesia. Factors used include financial distress, auditor's reputation, profitability and management changes The study is a population of companies listed on the Stock Exchange in the year 2009-2014. The total sample is 228 using purposive sampling method.Hypothesis testing is performed using logistic regression. The results of this study are auditor's reputation and management changes have effect on the change of KAP on manufacturing companies in Indonesia. While factors financial distress and profitability has no effect on the change of KAP on manufacturing companies in Indonesia.